Massively parallel read mapping on GPUs with the q-group index and PEANUT - Köster, Johannes; Rahmann, Sven (PeerJ, 2014)
We present the q-group index, a novel data structure for read mapping tailored towards graphics processing units (GPUs) with a small memory footprint and efficient parallel algorithms for querying and building. On top of the q-group index we introduce PEANUT, a highly parallel GPU-based read mapper. PEANUT provides the possibility to output both the best hits or all hits of a read. Our benchmarks show that PEANUT outperforms other state-of-the-art read mappers in terms of speed while maintaining or slightly increasing precision, recall and sensitivity.
Keywords: Read mapping; Datastructure; Parallel algorithms; GPU programming